2017
DOI: 10.5539/jel.v7n1p71
|View full text |Cite
|
Sign up to set email alerts
|

Opinions of Physical Education Teachers on the Concept of Sportsmanship

Abstract: The purpose of this study is to evaluate the opinions of physical education teachers on the concept of sportsmanship. This study, which has been based on the qualitative research paradigm, involves opinions of 13 physical education teachers (9 males and 4 females) which serve in public schools of Turkey and which have been specified through a critical incident sampling. A “semi-structured interview form” which has been developed using a literature review and expert opinions has been used to collect data. The d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…This is even more concerning because it turns out that Physical Education teachers have a narrow understanding of character, teachers also have not constructed character into students' cognitive reasoning during learning or sports activities carried out at school. The results of this study are in line with the results of research abroad conducted by (Koc & Esenturk, 2017) which show a lack of understanding of Physical Education teachers about how to carry out character learning to students.…”
Section: Introductionsupporting
confidence: 84%
“…This is even more concerning because it turns out that Physical Education teachers have a narrow understanding of character, teachers also have not constructed character into students' cognitive reasoning during learning or sports activities carried out at school. The results of this study are in line with the results of research abroad conducted by (Koc & Esenturk, 2017) which show a lack of understanding of Physical Education teachers about how to carry out character learning to students.…”
Section: Introductionsupporting
confidence: 84%
“…Another finding from this study dealt with aggressive behaviors during a competitive game, specifically taunting and boasting to an opponent. From the literature Koc (2018) examined the relationship between the PE course sportsmanship behaviors, tendency to violence and empathetic ability for elementary school 5 th grade students. The results showed that females had higher sportsmanship, lesser violent tendencies, and higher levels of empathy.…”
Section: Discussionmentioning
confidence: 99%
“…The PA classes can provide a vehicle for learning to cooperate with teammates, negotiate and reach solutions for moral conflicts, develop self-control, display courage, and learn virtues such as fairness, team loyalty, and persistence (Shields & Biedermeier, 1995;Stornes & Ommundsen, 2004;Koc & Tamer, 2016). Sportsmanship has been defined as a concern and respect for the rules and officials, social conventions, the opponent, as well as one's full commitment to one's sport and the relative absence of a negative approach towards sport participation (Bolter, Kipp & Johnson, 2018;Koc & Esenturk, 2018;Pennington, 2017;Vallerand et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…For example, we can use sportsmanship to evaluate the toughness of an athlete's will, but we cannot conclude that the athlete has good sports moral character. Moreover, in a study investigating teachers' and students' views on the concept of sportsmanship, Koç and Esentürk (46) found that teachers and students also regard "gentlemanship" and "making right decisions under tough conditions" as important contents of sportsmanship. In general, sportsmanship can be applied at the psychological and moral levels as well as to the expression of culture, thought, and ability in sports.…”
Section: Relationship Between Sports Moral Character and Sportsmanshipmentioning
confidence: 99%